Guidelines to Increase Potential of Tourist Attraction and Tourism Logistics Management Development in Nakhon Pathom Province - Ruangkalapawongse, Annop; Ruangkalapawongse, Sarawan (Dusit Thani College Journal, 2020)
The objectives of this research are to 1) study factors influencing tourist satisfaction in tourist attractions in Nakhon Pathom Province and 2) provide approaches to enhance the potential of tourist attractions and tourism logistics management in Nakhon Pathom Province. The method of this research is a mixed method between quantitative research and quantitative research. The quantitative approach applied a multi-stage sampling method and a questionnaire to obtain data from 400 samples including entrepreneurs, local people, tourists and government officials (tourism and sports division, the Sub-District Administrative Organization, Deputy Mayor of Mueang Rai Khing and Nakhon Chai Si Highway Division) and the data analysis was based on inferential statistics including Multiple regression analysis. The qualitative approach was used to explain and confirm the data obtained from the quantitative approach together with an in-depth interview with 13 samples. The qualitative data analysis was based on data analysis and conclusion. Findings of both quantitative and qualitative approaches corresponded to research objective 1 and 2 as follows: for objective 1, the factors influencing tourist satisfaction were facilities, information management, physical management and tourist attractions and the equation of tourist satisfaction in tourist attractions in Nakhon Pathom Province was: = 0.250 + 0.365 (facilities) + 0.275 (information management) + 0.232 (physical management) + 0.052 (tourist attractions). For objective 2, the approaches to enhance the potential of tourist attractions and tourism logistics management in Nakhon Pathom Province were divided into 3 levels which included tourism recovery plans for cultural sites and activities, tourism management plans aiming at elevating tourism for extensive recognition, and sustainable tourism plan aiming at attracting new tourists and increasing revisit rate.